PELAKSANAAN KONSERVASI MATA AIR BATIK WAIR DI DESA LELA KECAMATAN LELA KABUPATEN SIKKA - Fitri, Yohanista; Samin, Mikael; Pamungkas, Bella Theo Tomi (Jurnal Geografi, 2022)
The objectives of the research are (1) to find out the implementation of Batik Wair spring conservation in Lela sub-district, Sikka Regency (2) to find out the impact of Batik Wair spring conservation to the community in Lela Village, Lela District, Sikka Regency (3) to find out the impact of Batik Wair spring conservation Wair to the Batik Wair spring environment. The method used in this research is descriptive qualitative research method with data collection techniques, namely interviews, observation and documentation.The results showed that the implementation of the Batik Wair Spring Conservation in Lela village, Lela sub-district carried out by the village government, the community and the PDAM in the Lela area. Conservation implementation activities carried out by carrying out conservation activities for the spring area, making spring cover buildings, saving water use and local cultural traditions. The implementation of conservation Batik Wair springs provides benefits for the community, namely the community feels the freshness that coming from the spring forest, because the forest is not cut down randomly, the community has the belief the spring will continue to exist for the next generation. The implementation of the conservation of Batik Wair springs has an impact on the environment, namely the implementation of terracing carried out during the King's era where the springs reappeared, to prevent flood and erosion from occurring, as a storage medium for water reserves and the implementation of this conservation can ensure the availability of water.